The Influence of Environment and Managerial Capacity on Funding Decisions for Small Bamboo Bag Craft Businesses in Gowa Regency - Nahriana, Nahriana (International Journal of Education, Vocational and Social Science, 2023)
This research aims to determine the influence of the environment and managerial capacity on funding decisions for small bamboo craft businesses. This research was conducted in October 2023, the data used was primary and secondary data. Primary data was obtained through interview surveys using questionnaires and documentation. The data analysis used in this research is qualitative descriptive analysis and the data obtained is presented in tabular form. The results show that the process of empowering bamboo craftsmen in Lassalassa Village occurs through the implementation of empowerment which includes the awareness and behavior formation stage, the knowledge transformation stage, and the intellectual ability improvement stage. Implementation of empowerment is carried out through entrepreneurship training which includes two objectives, namely providing counseling to improve product quality and providing training in product development and marketing strategy skills. As well as assistance provided by the Department.